ANALYSIS AND PREDICTION OF THE BANKRUPTCY RISK IN ROMANIAN BUILDING SECTOR COMPANIES - Bărbuţă-Mişu, Nicoleta; Codreanu, Elena-Silvia (Ekonomika, 2014)
Abstract. In this study, the bankruptcy risk of the companies acting in the Romanian building sector was evaluated. The main purpose of this paper is to present, using the scoring method, the classification of enterprises according to their financial performance into both successful and bankrupt companies, To achieve this goal, we used two well-known models: Conan & Holder, and Altman. Based on financial data for the period 2008–2012, we performed a comparative analysis of bankruptcy risk and noted that the same company could be classified differently by these two models. The results may constitute a landmark for Romanian companies in substantiating decisions and in order to analyze the financial failure from at least two perspectives. Key words: scoring method, failure risk, bankruptcy prediction, financial ratios, discriminant analysis